2014
DOI: 10.1007/s10943-014-9967-3
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual and Religious Attitudes in Dealing with Illness in Polish Patients with Chronic Diseases: Validation of the Polish Version of the SpREUK Questionnaire

Abstract: Although providing religious/spiritual (SpR) support to sick has received in Poland growing attention in the scientific literature, little has been written about how to measure whether patients are in search for SpR or may already have trust in such a resource helpful to cope with disease. The Polish version of the SpREUK questionnaire was validated in a sample of 275 patients with chronic diseases. Both explorative and confirmatory factor analysis confirmed the already established three subscales, i.e., Searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…In fact, a study among Polish cancer patients by Wnuk et al, [38] confirmed a positive relationship between frequency of spiritual experiences and strength of hope. Indeed, the ability to reflect life concerns and to change life or behaviour (Reflection scale), which was also related in this study to the disease interpretation Value, has clearly a religious connotation and is strongly associated with positive views of God, also the experience of gratitude and awe [22].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In fact, a study among Polish cancer patients by Wnuk et al, [38] confirmed a positive relationship between frequency of spiritual experiences and strength of hope. Indeed, the ability to reflect life concerns and to change life or behaviour (Reflection scale), which was also related in this study to the disease interpretation Value, has clearly a religious connotation and is strongly associated with positive views of God, also the experience of gratitude and awe [22].…”
Section: Discussionmentioning
confidence: 55%
“…Referring to 15 items, it differentiates three factors, i.e., Search, Trust and Reflection (Büssing, 2010). Confirmatory factor analysis confirmed the already established three subscales also in SpREUK's Polish version with good internal consistency coefficients ranging from alpha 0.74 to 0.91, yet with 10 items (SpREUK-Polish) [22]:  Search scale, or search (for support/access to spirituality/religiosity), deals with patients' intention to find access to a spiritual or religious resource, which may be beneficial for coping with illness, and with their interest in spiritual or religious issues (insight and renewed interest).  Trust scale, or trust (in higher guidance/source), is a measure of intrinsic religiosity; the factor deals with patients' conviction that they want to be connected with a higher source, and with their desire to be sheltered and guided by that source, whatever may happen to them, conviction that death is not an end.…”
Section: Spirituality/religiosity and A Resourcementioning
confidence: 52%
See 1 more Smart Citation
“…We began with the validation of the Spiritual Needs Questionnaire in its Polish version [38], followed by the SpREUK questionnaire, which was developed to investigate whether or not patients with chronic diseases rely on spirituality as a resource to cope with illness [39]. Here, we report the validation of the Polish version of the SpREUK-P questionnaire, as applied among Polish patients with chronic diseases, which was designed to measure the engagement frequencies of a large spectrum of organized and private religious, spiritual, existential and philosophical practices.…”
Section: Aim Of This Studymentioning
confidence: 99%
“…Confirmatory factor analysis would indicate the 10 item version of the SpREUK (shortened Polish version = SpREUK-SV) to be more suited in the Polish sample [39]. Because we intended to compare the data of the Polish sample with other patient samples, we will use the respective scales with all items verified by exploratory factor analysis (SpREUK-Polish with 15 items).…”
Section: Spreuk-15 Scalementioning
confidence: 99%